The Historical Meaning and Functions of Scent From Rituals to Political Power - Meryem Gök; İlkay Şahin (Uluslararası Halkbilimi Araştırmaları Dergisi)
Smell is an important cultural tool that has shaped social structure and interactions, beyond being an individual taste. This study examines the social and cultural seductiveness of scent, its social psychological effects and functions in interpersonal relationships in the context of a historical process. Within this framework, its functions in cultural and religious rituals, its emotional and cognitive effects have been discussed, and its seductiveness in social relations and how it is used in persuasion processes in the historical process from the Egyptian queen Cleopatra to the modern period have been analysed in general. Cleopatra was chosen as an example in this study due to her historical and socio-political identity, which is known for directing persuasion processes by using odour and other sensory elements in addition to her political intelligence and diplomatic skills. The research evaluates the effect of scent on memory and emotion within the framework of Baudrillard’s theory of seduction. It also investigates the role of scent in the formation of both individual and collective identities through the development of the perfume industry. Additionally, the sociological meaning of scent is discussed through Weber’s concepts of status groups and charismatic authority. The findings of the study show that odour has played a dominant role in social and psychological interactions from the past to the present, creating multifaceted effects in the context of cultural norms and power relations beyond individual aesthetic understanding.